Long-term safety and dose escalation of intracerebroventricular CLN5 gene therapy in sheep supports clinical translation for CLN5 Batten disease - Mitchell, Nadia L.; Murray, Samantha J.; Wellby, Martin P.; Barrell, Graham K.; Russell, Katharina N.; Deane, Ashley R.; Wynyard, John R.; Palmer, Madeleine J.; Pulickan, Anila; Prendergast, Phillipa M.; Casy, Widler; Gray, Steven J.; et al. (Frontiers in Genetics, 2023)
CLN5 neuronal ceroid lipofuscinosis (NCL, Batten disease) is a rare, inherited fatal neurodegenerative disorder caused by mutations in the CLN5 gene. The disease is characterised by progressive neuronal loss, blindness, and premature death. There is no cure. This study evaluated the efficacy of intracerebroventricular (ICV) delivery of an adeno-associated viral vector encoding ovine CLN5 (scAAV9/oCLN5) in a naturally occurring sheep model of CLN5 disease. CLN5 affected (CLN5 -/-) sheep received low, moderate, or high doses of scAAV9/oCLN5 at three disease stages. The treatment delayed disease progression, extended survival and slowed stereotypical brain atrophy in most animals. Of note, one high dose treated animal only developed mild disease symptomology and survived to 60.1 months of age, triple the natural life expectancy of an untreated CLN5 -/-sheep. Eyesight was not preserved at any administration age or dosage. Histopathologic examination revealed that greater transduction efficiency was achieved through higher ICV doses, and this resulted in greater amelioration of disease pathology. Together with other pre-clinical data from CLN5 -/-sheep, the safety and efficacy data from these investigational new drug (IND)-enabling studies supported the initiation of the first in-human CLN5 gene therapy clinical study using the ICV delivery route for the treatment of CLN5 NCL (https://clinicaltrials.gov/; NCT05228145).